A Comparative Linguistic Analysis of the Initial six Letters of the Alphabet - Hoz Omer Rostam, Asst Lect.; . Hiwa Omer Salih, Asst Lect (lark, 2025)
This study is a phonetic morphological analysis using seven Arabic letters: Hamza, Ba, Ta, Tha, Jim, and Ha. We compared these letters with those of other Semitic alphabets. We chose to focus on the Hamza Because of it's great importance letters. Hamza is a consonant sound in the Semitic alphabets, represented by the alif in Arabic. It has retained its form in the Arabic script, although it has disappeared in pronunciation in some of the other Semitic languages.
Keywords: The alphabet letters/ Study/ Comparative linguistics.